Evaluating Program Enhancements for Mentors Working with Children of Incarcerated Parents (COIP), United States, 2016-2020 - Rhodes, Jean ([Verlag nicht ermittelbar], 2022)
The Children of Incarcerated Parents (COIP) Project was established as a means of evaluating mentorships between children whose parents are incarcerated and program mentors. This establishment was done as a result of the fact that over half of currently incarcerated Americans are parents, and over half of children whose parents are incarcerated are below the age of 10. The consequences of children having parents incarcerated can include family instability and possible future criminal activity of such children. The COIP Project was implemented across various mentorship programs throughout the United States with the objective of countering these issues.